PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Sukir, Suprayitno & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2007)
ABSTRACT The population in this research is 200 officers of Sub Office of city planning and Cleaning Service of Public Works and transportation Traffic Department of Karanganyar Regency. The research employed 40 respondents or 20 percent of the population’s number as the sample of the study because of the limitation of the researcher. The result of t test performed that: job discipline variable contributed the significant effect to the Performance of the officers of Sub Office of city planning and Cleaning Service of Public Works and transportation Traffic Department of Karanganyar Regency. It was showed by the significance value as many as 0,016. The work environment variable significantly affected to the Performance of the officers of Sub Office of city planning and Cleaning Service of Public Works and transportation Traffic Department of Karanganyar Regency performed by the significance value as many as 0,014. Meanwhile, the job motivation variable affected the performance of the officers of Sub Office of city planning and Cleaning Service of Public Works and transportation Traffic Department of Karanganyar Regency significantly. Its significance value was 0,006. The result of the determination coefficient test performed that the adjusted R square value was 0,533. It means that the free variable of job discipline and job motivation can elaborate the binding variable of to the Performance of the officers of Sub Office of city planning and Cleaning Service of Public Works and transportation Traffic Department of Karanganyar Regency; it is 53,3 percent  and the 46,7 percen  left is elaborated by the other variables which did not be studied by the writer, such as the control, compensation, the job satisfaction, the job experience, etc.Keywords : job discipline, work environment, job motivation, performance